Examining the effects between job characteristics, transformational leadership and meaningful work on employees of Taiwan SMEs - Kuo, Wei Ting (2019)
Meaningful work is a major factor for contemporary employees, and it can produce positive work outcomes. However, research exploring small and medium-sized enterprise (SME) employees’ perception of meaningful work in Taiwan or East Asia is scarce. Hence, this study examines the effect of the relationship between meaningful work, transformational leadership and job characteristics on employees of Taiwanese SMEs (N = 219). The results indicate a positive relationship between a supervisor’s transformational leadership behaviour, job characteristics and an employee’s meaning of work. Moreover, job characteristics partially mediate the relationship between transformational leadership and meaningful work.